2022
DOI: 10.1515/mgmc-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate temperature on structural, optical, and photoelectrochemical properties of Tl2S thin films fabricated using AACVD technique

Abstract: Thin films of thallium sulphide (Tl2S) were grown on the FTO surface at three different temperatures (500°C, 550°C, and 600°C) using the aerosol-assisted chemical vapor deposition approach. A thallium diethyldithiocarbamate (Tl[CNS2(C2H5)3]) complex was used as a single-source precursor in tetrahydrofuran (THF) solvent under an inert atmosphere of argon in all deposition experiments. The impact of deposition temperature on structural, morphological, and optical properties of Tl2S thin films was explored using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…12 Daraz et al demonstrated that the photoelectrochemical measurement in terms of linear sweep voltammetry confirms that the temperature variation has a significant effect on the photoconversion efficiency of Thalium Sulphide Thin films, and photocurrent density increases with deposition temperature. 13 Mansoor et al demonstrated that the Ceramic composite CdO-Mn 2 O 3 composite thin film semiconductor electrode exhibits n-type behaviour and the photocurrent density was found to be dependent on the deposition medium. 14 Among the versatile methods for the production of thin film gas sensors, [15][16][17][18][19][20][21] spray pyrolysis is the most convenient method because of its simplicity, low cost, easiness of adding doping materials, and the possibility of varying the film properties by changing composition of starting solution.…”
mentioning
confidence: 99%
“…12 Daraz et al demonstrated that the photoelectrochemical measurement in terms of linear sweep voltammetry confirms that the temperature variation has a significant effect on the photoconversion efficiency of Thalium Sulphide Thin films, and photocurrent density increases with deposition temperature. 13 Mansoor et al demonstrated that the Ceramic composite CdO-Mn 2 O 3 composite thin film semiconductor electrode exhibits n-type behaviour and the photocurrent density was found to be dependent on the deposition medium. 14 Among the versatile methods for the production of thin film gas sensors, [15][16][17][18][19][20][21] spray pyrolysis is the most convenient method because of its simplicity, low cost, easiness of adding doping materials, and the possibility of varying the film properties by changing composition of starting solution.…”
mentioning
confidence: 99%